2010
DOI: 10.1007/s10459-010-9224-9
|View full text |Cite
|
Sign up to set email alerts
|

Internal structure of mini-CEX scores for internal medicine residents: factor analysis and generalizability

Abstract: the mini-CEX appears to measure a single global dimension of clinical competence. If educators desire to measure discrete clinical skills, alternative assessment methods may be required. Our approach to factor analysis overcomes the limitation of repeated observations on subjects without discarding data, and may be useful to other researchers attempting factor analysis of datasets in which individuals contribute multiple observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
3
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 33 publications
4
45
3
5
Order By: Relevance
“…16 Further work has also suggested that examiners are a substantial source of variance in mini-CEX scores 17 and this reinforces the need for multiple, and different, examiners to assess a single student. 18 The use of multiple examiners and multiple patient encounters contributes to the reliability of the mini-CEX, 11,13,19,20 particularly with one assessor per encounter and different assessors for each encounter. 19 There are varying reports as to the number of encounters required to obtain a reliable result.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Further work has also suggested that examiners are a substantial source of variance in mini-CEX scores 17 and this reinforces the need for multiple, and different, examiners to assess a single student. 18 The use of multiple examiners and multiple patient encounters contributes to the reliability of the mini-CEX, 11,13,19,20 particularly with one assessor per encounter and different assessors for each encounter. 19 There are varying reports as to the number of encounters required to obtain a reliable result.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…19 There are varying reports as to the number of encounters required to obtain a reliable result. Authors have reported between that 6 to 15 encounters are required 8,[19][20][21][22][23][24] and this number appears to be feasible in different training settings. 25 As far as usability is concerned, the mini-CEX has been reported to be easily implemented into day-to-day practice and has broad applicability in a variety of settings and provides students with well-timed feedback.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Determining the clinical competence of a cohort of students from performance in one interview, particularly given a common tendency to perform differently when being viewed by others (Clauser et al 2012), may not provide a valid view of their competence (Panzarella and Manyon 2007). In view of these factors, the use of the SPIRS as a means of providing formative assessment for students is appropriate, but caution should be exercised in its use as a high-stakes summative assessment (Cook et al 2010).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…19 The construct validity of mini-CEX use with residents is well demonstrated. [20][21][22][23][24][25] Consistent with the precepts of competency-based education, the assessments evaluate the presence or absence of observable behaviors, rather than using scales or judgments of relative skill. Drafts of the tools were e-mailed to the 14 faculty preceptors, who subsequently met to discuss revisions.…”
Section: Methodsmentioning
confidence: 99%